2021
DOI: 10.1111/jgh.15550
|View full text |Cite
|
Sign up to set email alerts
|

SETD8 involved in the progression of inflammatory bowel disease via epigenetically regulating p62 expression

Abstract: Background and Aim: Epigenetic modification is an important part of the pathogenesis of inflammatory bowel disease (IBD). Some studies proved that p62 was involved in inflammatory response and upregulated in IBD patients, and histone modification plays an important role in regulating p62 expression. SETD8, a histone H4K20 methyltransferase, has been reported downregulated in some inflammatory diseases. Here, we investigated the role of SETD8 in the development of IBD and its underlying mechanisms. Methods: An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…A large proportion of genes enriched in newly diagnosed pediatric IBD patients maintained a significant level of H3K4me3, which was related to the severity of intestinal inflammation during the progression of IBD ( 34 ). SETD8 is a typical histone H4K20 methyltransferase in which silence of SETD8 could significantly decrease the enrichment of H4K20me1 in the p62 promoter to regulate the expression of p62 and inhibit the inflammatory response in colitis ( 35 ). The level of H3K9 acetylation was decreased upon dextran sulfate sodium (DSS) treatment, which was reported to induce colitis by lessening the macrophage amount and the secreted inflammatory cytokines ( 188 ).…”
Section: Histone Modifications In Inflammatory Diseasesmentioning
confidence: 99%
“…A large proportion of genes enriched in newly diagnosed pediatric IBD patients maintained a significant level of H3K4me3, which was related to the severity of intestinal inflammation during the progression of IBD ( 34 ). SETD8 is a typical histone H4K20 methyltransferase in which silence of SETD8 could significantly decrease the enrichment of H4K20me1 in the p62 promoter to regulate the expression of p62 and inhibit the inflammatory response in colitis ( 35 ). The level of H3K9 acetylation was decreased upon dextran sulfate sodium (DSS) treatment, which was reported to induce colitis by lessening the macrophage amount and the secreted inflammatory cytokines ( 188 ).…”
Section: Histone Modifications In Inflammatory Diseasesmentioning
confidence: 99%
“…The treatment started on day 0 and continued until the mice were sacrificed. The DAI score was used to quantify the severity of colitis, as previously described [ 66 ] and shown in Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that silencing SETD8 regulates the expression of the p62 protein, thus blocking the inflammatory response of the colon. The authors suggest that SETD8 may be used in the future as a potential therapy for patients with IBD [ 92 ]. Another study using Lactobacillus casei probiotic in mice with colitis investigated the effect of L. casei on the immune response and histone modifications.…”
Section: Epigenetic Factorsmentioning
confidence: 99%